>
数学
>
(-1/6x^2y)xxy^2x(-3xyz),3x(x-1)-5x(x+2),(3x+2)(2x-3),因式分解
人气:432 ℃ 时间:2019-08-21 19:17:13
解答
(-1/6x^2y)xxy^2x(-3xyz),
=1/2x^4y³z
3x(x-1)-5x(x+2),
=3x²-3x-5x²-10x
=-2x²-13x
(3x+2)(2x-3)
=6x²-9x+4x-6
=6x²-5x-6
推荐
(2x-3y)^3 +(3x-2y)^3-125(x-y)^3 这个怎么因式分解
因式分解:(2x+3y)^2-(3x-2y)^2
因式分解 1、-25x的平方+4 2、(3x+2y)的平方-(2x+3y)的平方 3、 x的平方(a-1)+4(1-a)
(x+2y)∧2-3x(x+2y)因式分解
3x(x-1)-5x(x+2),(-1/6x^2y)乘xy^2乘(-3xyz),(3x+2)(2x-3)
两数和为3,积为-10 求这两个数
用英语简单描写你的房间
以我的卧室写一篇英语作文
猜你喜欢
carefully
After paying 1000 dollars ____,you will all become full memebers of our club A each B all c every
Our class has a map of the world (改为同义句)
The baby didn't cry any more when she saw her mother.同义句
How do you go to school,on foot or by bus?
时间旅行的悖论
设f(x)=ax7+bx5+cx3+dx+5,其中a,b,c,d为常数.若f(-7)=-7,则f(7)=_.
计算1-3+5-7+9-11+…+97-99.
© 2024 79432.Com All Rights Reserved.
电脑版
|
手机版